Strategi Pengembangan Usahatani Tembakau - Jaka Sulaksana; Didit Singgih Ginanjar; Sri Umyati (Paradigma Agribisnis, 2024)
Tobacco is one of the commodities that has enough potential to be developed, this is listed from the amount of foreign exchange and excise taxes obtained from tobacco. For this reason, the purpose of this study is directed to find out the business development strategy. The research method uses survey techniques with quantitative and qualitative approaches. 31 respondents used the purposive technique. The analysis techniques used are Descriptive analysis, SWOT analysis and QSPM. The results of this study showed that internal factors in the form of strengths and weaknesses owned by tobacco farmers in Bantarujeg District obtained a total internal factor evaluation (IFE) score of 3.29 and external factor evaluation (EFE) of 3.15. The company's Internal and External (IE) matrix is in cell 1 which means that the farm is in the Growth and Build area or grow and build. The strategy that can be applied is to apply the Intensive Strategy. Which includes market penetration, and development of agricultural products.From the results of the IFE and EFE Matrix analysis, it was found that the total score of the IFE Matrix for Tobacco Farming in Babakansari Village was 3.29, while the total score of the EFE Matrix for tobacco Business in Babakansari Village was 3.15.Keywords : Tabacum Farming, SWOT Analysis, QSPM